FLOWGAURD APPLICATION IN FLOODLIGHT FOR SECURED AND RELIABLEECURED SOFTWARE DEFINED NETWORKS - Harika, G; Rajaram, Dr. J; Raju, S; Reddy, E Muralidhar (The journal of contemporary issues in business and government, 2020)
Software-Defined Networking (SDN) provides network-wide access to programmers and direct control from a theoretically centralized controller over the underlying switches. SDN proposes a positive path for the Internet to grow in the future. However, SDN has several modern protection problems as well. How to develop a stable firewall programme for SDN is a vital task for them. Since the stateless property of the Open Flow-based SDN firewall lacks audit and monitoring mechanisms, current SDN firewall implementations may also be easily bypassed by rewriting the switch flow entries. Focusing on this hazard, by testing flow space and firewall authorization space, we implemented a novel approach for dispute detection and resolution in Open Flow focused firewalls. Unlike Fortnum, based on the whole flow paths inside an Open Flow network, our method will verify the contradictions between the firewall rules and flow policies. Finally, for flow tables and firewall guidelines, we introduced intra-table dependency testing.